The circle of continuous improvement and the use of geographical information systems (GIS) to control accidents at the Oil Exploration Company - علي, لمى عصام; خلف, بتول عطية (Journal of Petroleum Research and Studies, 2022)
The current research includes applying a cycle of continuous improvement and using geographic information systems for the purpose of controlling work accidents. (24) Incidents were selected as a sample for the period 2017-2018-2019 that took place in the Oil Exploration Company. The research problem was determined by the presence of accidents that affected the productivity of seismic teams and negatively and significantly affect the progress of production in terms of stopping work, slow completion, inaccuracy, loss of effort, in addition to the loss of competencies of geologists, engineers, and skilled workers, waste of time and work requirements, the method of applying the Deming Cycle was used. For continuous improvement and geographic information systems (GIS) technology by using ArcGIS 10.8 and studying the impact of improvement by analyzing some data spatially, the research has reached several results, the most important of which is the possibility of using geographic information systems to build databases that can be referred to avoid accidents among workers.